Physical training and mental preparation among Norwegian top-class football referees - Johansen, B. T.; Giske, R.; Haugen, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Johansen & Haugen (2013) have claimed that the role of the football referee requires a high degree of physical fitness as well as complex decision-making. Scientific knowledge related to elite football referees training and mental preparation was sporadic before the millennium, but it has increased slowly the last decade (Catteewu et al 2009). The aim of this study was to examine the amount of physical training and mental preparation among top-class referees in Norway. Methods: This cross-sectional study was conducted as a part of the "Norwegian Elite Referees in football"-study. A total of 83 from 98 (84.7%) top-ranked referees (73 males and 10 females) from age 20 to 46 (mean age 33.3 years) completed a questionnaire using, SurveyXact, a web based program for electronic questionnaires. The referees were asked to estimate how much (in hours per week) of the physical training was endurance training (running, cycling, skiing) and how much of this training was sprint related (interval training, strength fitness, football playing). Mental training was assessed from one item with 4 response categories (twice a week or more; once a week; less than once a week; never). Results: Results revealed that 85.5% (71/83) of the top-class referees conducted physical training five times or more per week. 14.6% (12/83) conducted physical training three times per week. A median (Q1 , Q3) of 5 (3 , 6) hours per week for endurance training and 2 (1 , 3) hours per week for sprint related training were also reported. Regarding mental training the referees reported the following: 6.2% twice a week or more; 30.9% once a week; 30.9% less than once a week; 32.1% never. Discussion: Due to the participation rate of nearly 85% of the Norwegian top-class referees, one may claim that they are conducting physical training according to the physicals demands of a football match at top flight level (Krustrup et al 2009). The frequency of mental training reported is rather partial. However, it is in line with findings from Catteeuw et al (2009).